Legality of Corruption Eradication Commission's Authority in Arresting Operations Against Corruption Cases Based on Indonesian Procedural Criminal Code - Amanda, Abraham (Law Research Review Quarterly, 2019)
The number of arrests carried out by the KPK lately, known as the Capture Operations or OTT, led to a polemic whether the action was legal or invalid. There are parties who consider that the OTT carried out by the KPK is illegal or illegal. The research used is a normative legal research method (normative juridical) by conducting a literature study to collect secondary data. Normative legal research is done by examining library materials (literature) which are secondary data. From the analysis that can be understood, the OTT Corruption Eradication Commission against suspects in corruption cases in relation to the term caught in the Criminal Procedure Code Article 111 paragraph (1) KUHAP and Article 1 point 19 KUHAP above the legal basis for the Corruption Eradication Commission in conducting Hand Arrest Operations (OTT ) which is considered illegal and considers that the Hand Arrest Operations are different from the Hand Caught contained in these articles. Then OTT in relation to the special investigation technique known as Controlled Delivery is often used by BNN investigators, assessing that the practice of KPK in OTT has used two such actions (interdiction and entrapment) which means KPK investigators have adopted without the authority that BNN investigators have, so that the KPK has committed three types of actions that violate the law (interdiction, entrapment and in the process of investigation).